AVAILABILITY OF PRINT AND INTERNET RESOURCES AS FACTORS INFLUENCING READING CULTURE OF SECONDARY SCHOOL STUDENTS IN EDO STATE, NIGERIA (2017)
Poor reading culture being exhibited by the secondary school students in Edo State is responsible for their inability to engage in critical thinking, sound analysis of events and situations, and poor academic achievement. Many studies have examined cognitive factors affecting reading culture with little attention on print and Internet resources. This study, therefore, investigated availability of print and Internet resources as factors influencing reading culture of secondary school students in Edo State, Nigeria. Skinner’s Behavioural theory provided the framework, while descriptive survey design of correlational-type was adopted. The population comprised Senior Secondary School students in both public and private secondary schools in Edo State. Multi-stage sampling procedure was adopted. Nine (three from each senatorial district) Local Government Areas (LGAs) out of 18 LGAs were randomly selected. Using purposive sampling technique, a total of 65 schools (50 public and 15 private secondary schools) were selected from the nine LGAs. A total of 819 students were randomly selected (49.0% males and 51.0% females). Instruments used were: Availability of print resources (r=0.87), Availability of Internet resources (r=0.82) and Reading culture (r=0.75) questionnaires. These were complimented with Key informant interview with five school principals each from public and private secondary schools. Descriptive statistics, Pearson product moment correlation and Multiple regression were used for analysis at 0.05 level of significance, while the qualitative data was content analysed. The age of the students was 16.4+1.91 years. The mean score for pubic secondary schools’ reading culture was 51.00, and for private secondary schools was 62.50. There was significant correlation between reading culture and print resources (r=0.16). There was significant correlation between reading culture and Internet resources (r=0.10). There was a significant joint contribution of availability of print and Internet resources on students’ reading culture (F(2,816), =12.55; R2 = 0.03) translating to 3.0% of its variance. Availability of print resources (β = 0.141) and Internet resources (β = 0.075) relatively contributed to reading culture. There was low reading culture among the students which was traced to poor mentoring, students’ inability to procure relevant texts and negative peer influence. Availability of print and Internet resources influenced reading culture of Senior Secondary School students in Edo State. Education policy makers and librarians should encourage revitalisations of readers’ club in the secondary schools in order to sustain reading culture